Arabic Microteaching Training to Improve the Teaching Competence of TPQ Ustaz/Ustazah - Biqi Zain; Maulana Purwa Rimba; Abdulloh Aziz Assa’diy (IMPACT: Journal of Innovation Mission and Community Service, 2025)
Microteaching training was conducted at the Al Muttaqiin Islamic Boarding School (TPQ) in Pacitan to improve the Arabic language teaching competencies of Islamic teachers (ustaz/ustazah), which have been diverse and unstructured. This activity aimed to strengthen pedagogical skills, the use of interactive methods, and communication and classroom management skills in Arabic language learning. The training included workshops, microteaching practices, direct feedback, and structured reflection. Results showed significant improvements in lesson planning, the variety of methods such as games, flashcards, and role-playing, and the ability to deliver clear, developmentally appropriate instructions. Participants responded positively, demonstrated by enthusiasm in discussions and practice. Furthermore, there were initial indications that students' learning became more active and enjoyable. Thus, microteaching has proven effective as a strategy to improve the quality of Arabic language learning at the TPQ.